Robotic-Assisted versus Laparoscopic Sleeve Gastrectomy: Comparison of Perioperative Outcomes - Kim Seung-hyun, Park Ji-hoon, Lee Min-jae (Academic Journal of Clinicians, 2024)
Background: Sleeve gastrectomy is a commonly performed bariatric surgical procedure. Robotic-assisted sleeve gastrectomy (RASG) has emerged as an alternative to the traditional laparoscopic approach (LSG), but the comparative perioperative outcomes between the two techniques are not well-established. Objectives: To compare the perioperative outcomes between RASG and LSG, including operative time, length of hospital stay, and complication rates. Methods: A retrospective analysis was conducted on patients who underwent either RASG or LSG at a single tertiary care center between 2018-2022. Demographic data, procedural details, and 30-day postoperative outcomes were collected and analyzed. Results: A total of 300 patients were included, with 150 patients in each the RASG and LSG groups. The mean operative time was significantly longer in the RASG group compared to the LSG group (145 minutes vs. 110 minutes, p<0.001). However, the RASG group had a shorter median length of hospital stay (2 days vs. 3 days, p=0.02) and a lower rate of overall postoperative complications (12% vs. 18%, p=0.04). Conclusions: Despite a longer operative time, RASG is associated with a shorter hospital stay and lower overall complication rates compared to the traditional laparoscopic approach. These findings suggest that RASG may be a safe and effective alternative for sleeve gastrectomy in appropriate patients.